The effectiveness of the promotional tools practiced by Pusat Zakat Melaka (PZM) / Norlela Abas - Abas, Norlela (Faculty of Business and Management, 2008)
The research of "The Effectiveness of Promotional Tools of Pusat Zakat Melaka (PZM) was conducted with four objectives which are first to determine the current level of the effectiveness of the promotional tools used by Pusat Zakat Melaka, second to identify the most effective promotional tools by PZM, third to study the relationship between selected respondent profiles with the total or overall effectiveness and fourth to recommend how to improve promotional tools for Pusat Zakat Melaka. The respondents of this study were the people who pay zakat at Pusat Zakat Melaka and 70 questionnaires had been distributed .The researcher had used Simple Random Sampling as the sampling technique. In this study, descriptive statistics had been used to interpret the data such as reliability testing, frequency tables. From the findings, the respondents agree with the effectiveness of promotional tools which is advertising (billboard & banners), radio, and event used by Pusat Zakat Melaka. While the most effective promotional tools that Pusat Zakat Melaka should implement is billboards and banners. The results also show the relationship between the promotional tools with the overall or total effectiveness. Most of the promotional tools used by PZM have a positive, significant and strong relationship with the promotional tools effectiveness significant with the 0.000 at < 0.05 level. Other than that, the research also shows the relationship between respondents' profile with the overall or total effectiveness. Beside, the research also came out with some recommendations in order to make the promotional tools of PZM become more effective and can create interest of Muslims to pay zakat. For example hold more public talk and exhibition, collaboration with government agencies and private sectors, and do a consistent advertisement in the radio and newspaper.